Quality Ladders and Product Cycles - Grossman, Gene M.; Helpman, Elhanan (Quarterly Journal of Economics, 1991)
We develop a two-country model of endogenous innovation and imitation in order to study the interactions between these two processes. Firms in the North race to bring out the next generation of a set of technology-intensive products. Each product potentially can be improved a countably infinite number of times, but quality improvements require the investment of resources and entail uncertain prospects of success. In the South entrepreneurs invest resources in order to learn the production processes that have been developed in the North. All R&D investment decisions are made by forward-looking, profit-maximizing entrepreneurs. The steady-state equilibrium is characterized by constant aggregate rates of innovation and imitation. We study how these rates respond to changes in the sizes of the two regions and to policies in each region to promote learning.